2019
DOI: 10.1186/s12941-019-0304-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of malaria rapid diagnostic tests results on antimicrobial prescription practices of health care workers in Burkina Faso

Abstract: BackgroundMalaria rapid diagnostic tests (RDT) are widely used in endemic areas in order to comply with the recommendation that malaria treatment should only be given after the clinical diagnosis has been confirmed by RDT or microscopy. However, the overestimation of malaria infection with the use of PfHRP2 based RDT, makes the management of febrile illnesses more challenging. This study aimed to assess the effect of the use of malaria RDT on antimicrobial prescription practices.MethodsA prospective study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…Deletions in the Pfhrp 2 gene that result in false negative malaria RDT results are detrimental and have the potential of missing malaria positive patients in countries like Ghana where testing is largely by PfHRP2 RDTs. The symptomatic malaria patients who test negative may likely not receive appropriate antimalarial treatment [13,14]. To ensure the maintenance of the diagnostic accuracy of malaria RDT results and prevent the misdiagnosis of malaria in the era of the WHO's Test Treat and Track initiative, the WHO partnered with the Foundation for Innovative New Diagnostics (FIND) to set up the WHO-FIND Malaria Evaluation Programme to provide quality assurance for the manufacture of malaria RDT kits [15].…”
Section: Introductionmentioning
confidence: 99%
“…Deletions in the Pfhrp 2 gene that result in false negative malaria RDT results are detrimental and have the potential of missing malaria positive patients in countries like Ghana where testing is largely by PfHRP2 RDTs. The symptomatic malaria patients who test negative may likely not receive appropriate antimalarial treatment [13,14]. To ensure the maintenance of the diagnostic accuracy of malaria RDT results and prevent the misdiagnosis of malaria in the era of the WHO's Test Treat and Track initiative, the WHO partnered with the Foundation for Innovative New Diagnostics (FIND) to set up the WHO-FIND Malaria Evaluation Programme to provide quality assurance for the manufacture of malaria RDT kits [15].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a study conducted in Burkina Faso evidenced a shift in health workers' attitudes when faced with negative RDT; they tended to prescribe antibiotics rather than ACT. The authors found that 92.89% of nurses were compliant with the rapid test result [63]. At a regional level, a multi-country study conducted in three West African countries, including Burkina Faso, showed an overall noncompliance rate below 1% in a small proportion (6.8%) of the community health workers (CHWs) involved.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria from animals are among the predominant causes of diseases in the food chain 2 . Even with the recognition of these facts, zoonotic infections frequently remain undiagnosed in humans and usually mistaken for other febrile diseases such as malaria among others 6 , 7 . The present success of animal husbandry has been linked to the use of antibiotics as growth promoters and in the prevention of infections but this may present a huge cost for the future.…”
Section: Introductionmentioning
confidence: 99%